A simple approach to the Visible-light photoactivation of molecular metal oxides - Fujimoto, Satomi; Cameron, Jamie M.; Wei, Rong Jia; Kastner, Katharina; Robinson, David; Sans, Victor; Newton, Graham N.; Oshio, Hiroki (American Chemical Society, 2017)
This study explores a new method to maximise the visible-light driven photocatalytic performance of organic-inorganic hybrid polyoxometalates (POMs). Experimental and theoretical investigations of a family of phosphonate substituted POMs shows that modification of grafted organic moieties can be used to tune the electronic structure and photo-activity of the metal oxide component. Unlike fully inorganic polyoxotungstates, these organic-inorganic hybrid species are responsive to visible-light and function as photocatalysts (λ > 420 nm) in the decomposition of a model environmental pollutant. The degree of photo-activation is shown to be dependent on the nature of the inductive effect exerted by the covalently-grafted substituent groups. This study emphasises the untapped potential that lies in an orbital engineering approach to hybrid-POM design and helps to underpin the next generation of bespoke, robust and cost-effective molecular metal oxide photo-active materials and catalysts.